2016
DOI: 10.1371/journal.pone.0159556
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis Disease Activity Is Determinant for ABCB1 and ABCG2 Drug-Efflux Transporters Function

Abstract: ObjectiveTo compare drug efflux function of ABCB1 and ABCG2 transporters in rheumatoid arthritis (RA) patients with active disease and in remission.MethodsTwenty two active RA patients (DAS28 ≥3.2) and 22 patients in remission (DAS28<2.6) were selected from an early RA clinic. All patients were evaluated at study inclusion and six months later. ABCB1 and ABCG2 functional activity was measured in peripheral lymphocytes by flow cytometry. The percentage of cells able to extrude substrates for ABCB1 and ABCG2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…As an efflux transporter, BCRP is highly expressed in apical epithelium of small intestine and colon, which can restrict the absorption of its substrates 42 . Recent studies have shown the importance of BCRP in diabetes 43 , rheumatoid arthritis 44 and various cancers 45 , 46 .…”
Section: Application Of Intestinal 3d Organoids In Drug Transport Researchmentioning
confidence: 99%
“…As an efflux transporter, BCRP is highly expressed in apical epithelium of small intestine and colon, which can restrict the absorption of its substrates 42 . Recent studies have shown the importance of BCRP in diabetes 43 , rheumatoid arthritis 44 and various cancers 45 , 46 .…”
Section: Application Of Intestinal 3d Organoids In Drug Transport Researchmentioning
confidence: 99%
“…In humans, over 20 ABC transporters, covering all sub-families, have been found to associate with human diseases (Theodoulou and Kerr, 2015). Several ABC transporters also play an important role in drug metabolism and resistance (Atisha-Fregoso et al, 2016). The role of eukaryotic ABC transporters in RA has been studied for almost two decades (Marki-Zay et al, 2013).…”
Section: Identification and Evaluation Of 94 Microbial Adhesive Protementioning
confidence: 99%
“…with drug resistance, disease activity, and progressive destructive arthritis with extra-articular involvement in RA (Atisha-Fregoso et al, 2016;Pascual-Ramos et al, 2016). P-glycoprotein (Pgp), a member of the eukaryotic ABC transporter superfamily, can stimulate CXCR4-overexpressing B cells, and produce rheumatoid factor and various inflammatory cytokines, such as tumor necrosis factor (TNF) and interleukin (IL)-6, and present antigens to T cells in RA (Tsujimura et al, 2018).…”
Section: Identification and Evaluation Of 94 Microbial Adhesive Protementioning
confidence: 99%
“…К сожалению, не так много работ, в которых анализируются детерминанты функциональной активности этих транспортеров при РА, в большинстве из них изучали ABCB1. Специальное исследование показало, что у больных активным РА повышена функция ABCB1 и ABCG2 и активность болезни тесно связана с этим феноменом [29].…”
Section: о с н о в а н и я д л я о т м е н ы т б п в п г и б п и т unclassified